Do perceived value and satisfaction affect customers’ behavioural intentions? A case study of Polish squash clubs - Monika Piątkowska (Journal of Marketing and Consumer Behaviour in Emerging Markets)
The aim of the paper is to analyze relations between perceived quality, service convenience and satisfaction of squash customers to present implications for managers who address parents enrolling their children for extracurricular activities with their services. Applying the research framework of García-Fernández et al. (2018), a sample of 120 parents from Legia Warszawa Squash Academy completed an online survey in 2021. The SEM model revealed that perceived quality as well as service convenience had a positive and significant effect on perceived value, which turned out to be a strong predictor of customer satisfaction. Finally, satisfaction showed a very strong positive and significant influence on behavioral intentions of squash customers. The present study makes both a theoretical and a practical contribution to the field of sports management, highlighting the importance of perceived quality and service convenience to deliver expected value to the customer.